Innovative Immigration Management Services from the Perspective of International Migrant Integration: A Focus on the United States Green Card System - Qi, Lixin; Ma, Zhihui; Chen, Hongtao; Bo, Yufeng; Meng, Han (International Journal of Social Sciences and Public Administration, 2024)
This paper explores the advantages of the United States Green Card system and its impact on the social integration of international migrants. It discusses the importance of innovative immigration management services in facilitating migrant integration and highlights the benefits of the Green Card system in enhancing economic, social, and cultural integration. The study finds that while the U.S. Green Card system provides significant advantages for migrants, there are still challenges that need to be addressed through service innovations and policy improvements.